RADIOGRAPHIC IMAGING OF STEEL OVAL LOCK CARABINER BY USING COMPUTED RADIOGRAPHY: A PILOT STUDY - Mohamad Radzi, Nadzirah; Abdul Majid, Zafri Azran (International Journal of Allied Health Sciences, 2018)
Introduction: Carabiner is one of Personal Protective Equipments (PPE), which is used to protect the users from hazards by reducing any chance of serious injury. Thus, it is very important to detect even a small defects on the component before it becomes worsen that could give harm to the users. The aim of this paper is to find out the appropriate imaging technical factors of steel carabiner by using computed radiography (CR). Methods: Radiographic images of carabiner were obtained by manipulating the values of kVp and mAs with respect to contrast and density. A preliminary study was carried out to determine the exposure factor combination in order to produce perceptible visual quality of radiographic images. Positioning techniques applied in this study were whole view (open-gate and close-gate position) and screw view (open-gate and close-gate position). An assessor was invited to evaluate the radiographs by using Image Quality Criteria Scoring (ICS) adapted from European Guidelines on Quality Criteria for Diagnostic Radiographic Images. Results: Findings showed that the optimum values of kVp and mAs in imaging whole view (open-gate and close-gate) carabiner were 133 kVp and 28 mAs while, for screw view (open-gate and close-gate) the range of kVp and mAs preferred were 121 kVp to 133 kVp and 28 mAs to 36 mAs respectively. Conclusion: This study has found that the use of medical CR to expose metal steel such as carabiner is accepted. By manipulating the imaging parameters, CR is able to produce an image of carabiner with a good quality.